2023
DOI: 10.1210/endocr/bqad069
|View full text |Cite
|
Sign up to set email alerts
|

The REV-ERB Nuclear Receptors: Timekeepers for the Core Clock Period and Metabolism

Abstract: REV-ERB nuclear receptors are potent transcriptional repressors that play an important role in the core mammalian molecular clock and metabolism. Deletion of both REV-ERBα and its largely redundant isoform REV-ERBβ in a murine tissue-specific manner have shed light on their specific functions in clock mechanisms and circadian metabolism. This review highlights recent findings that establish REV-ERBs as crucial circadian timekeepers in a variety of tissues, regulating overlapping and distinct processes that mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 155 publications
0
11
0
Order By: Relevance
“…Recently, attention has turned to the development of pharmacological compounds designed to target Rev-erb and ROR nuclear receptors within the circadian mechanism, offering potential clinical applications [ [36] , [37] , [38] ] [ [36] , [37] , [38] ] [ [36] , [37] , [38] ]. The administration of Rev-erbα agonists to mice has shown promise in treating metabolic disorders and improving inflammatory processing [ [39] , [40] , [41] ] [ [39] , [40] , [41] ] [ [39] , [40] , [41] ]. Additionally, various micro-RNAs have been identified that target Bmal1 to regulate circadian rhythms [ [42] , [43] , [44] ] [ [42] , [43] , [44] ] [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attention has turned to the development of pharmacological compounds designed to target Rev-erb and ROR nuclear receptors within the circadian mechanism, offering potential clinical applications [ [36] , [37] , [38] ] [ [36] , [37] , [38] ] [ [36] , [37] , [38] ]. The administration of Rev-erbα agonists to mice has shown promise in treating metabolic disorders and improving inflammatory processing [ [39] , [40] , [41] ] [ [39] , [40] , [41] ] [ [39] , [40] , [41] ]. Additionally, various micro-RNAs have been identified that target Bmal1 to regulate circadian rhythms [ [42] , [43] , [44] ] [ [42] , [43] , [44] ] [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in mammals, the circadian transcription factors BMAL (brain and muscle ARNT-like) and CLOCK (circadian locomotor output cycles kaput) bind to promoters for Per (period) and CRY (cryptochrome), driving expression of these proteins, which then inhibit BMAL and CLOCK over the course of 24 hours 2 (Figure 1). There is a second negative feedback loop whereby BMAL is regulated by the REV-ERB (nuclear receptor subfamily 1 group D) transcription factors, 2,3 adding another layer of complexity to our intrinsic cellular timing system (Figure 1). The discovery of this molecular clock in drosophila won the Nobel Prize in 2017, 4 enabling scientists to better understand the driving mechanisms of pathology after circadian disruption.…”
Section: Basics Of Circadian Rhythmsmentioning
confidence: 99%
“…]methyl]cyclopentanamine Dihydrochloride (18). Compound 18 was prepared according to the general procedure N using aldehyde 40k (0.056 g, 0.23 mmol), amine 30e (0.041 g, 0.23 mmol), and NaBH(OAc) 3 (0.098 g, 0.46 mmol) in anhydrous CH 2 Cl 2 (2.30 mL).…”
Section: Synthesis Of Rac-1-(4-fluorophenyl)-n-[[3-[[122-trimethyl-4p...mentioning
confidence: 99%